2001
DOI: 10.1007/pl00007093
|View full text |Cite
|
Sign up to set email alerts
|

Oral α adrenoceptor blockade as a treatment of erectile dysfunction

Abstract: The sympathetic nervous system, via release of noradrenaline (NA) and stimulation of alpha adrenoceptors (ARs), is considered to be the prime determinant of cavernosal smooth muscle contraction and detumescence. A relative predominance of NA-induced contraction over nitric oxide-mediated relaxation may contribute to erectile dysfunction (ED). Therefore alpha AR antagonism seems an attractive way of treating ED, but so far the therapeutic success of oral treatment has been limited. Modest activity has been docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…5 It has been demonstrated that intracavernous injection of a-adrenergic agonists results in maximum contraction 8 while antagonists produce erections. 9 Similar results have been demonstrated ex vivo using isolated smooth muscle cells from human penile corpus cavernosum. 10 The role of NA is not limited to the peripheral nervous system.…”
Section: From Physiology To Pathologysupporting
confidence: 73%
“…5 It has been demonstrated that intracavernous injection of a-adrenergic agonists results in maximum contraction 8 while antagonists produce erections. 9 Similar results have been demonstrated ex vivo using isolated smooth muscle cells from human penile corpus cavernosum. 10 The role of NA is not limited to the peripheral nervous system.…”
Section: From Physiology To Pathologysupporting
confidence: 73%
“…As an example, alprostadil acts as a PGE1 agonist and affects the adenylate cyclase (AC)-cAMP pathway [28,29]. Besides this, inhibition of the vasoconstriction is another possible strategy that could be pursued opportunely interacting with endothelin [30], angiotensin [31], and adrenergic receptors [32].…”
Section: Alternative Targetsmentioning
confidence: 99%
“…81 In patients with erectile insufficiency oral or buccal phentolamine has shown some success. 82,83 Phentolamine also blocks a 1 and a 2 -adrenoceptors in the systemic arterial circulation and therefore, hypotension is the major adverse effect of phentolamine. The hypotensive action of phentolamine is followed by compensatory reflex cardiac stimulation by tachycardia, and the latter response is blunted in patients treated with badrenoceptor antagonists.…”
Section: A-adrenoceptor Antagonists and Drugs For Cardiovascular Diseasementioning
confidence: 99%